The Influence of Whiteboard Animation Media on the Creative Thinking Abilities of Sixth-Grade Mathematics Learning - Ramdani, Rizki; Yuliyanto, Aan; Muzfirah, Suci; Rochim, Ahmad Abdul; Ripai, Akhmad (International Conference on Elementary Education, 2024)
The importance of creative thinking skills is that students can have understanding or ideas to find new solutions to the problems they face every day. This Literature Review is motivated by improving elementary school students' creative thinking abilities in mathematics learning. This Literature Review aims to improve elementary school students' creative thinking skills in mathematics through whiteboard animation learning media. Whiteboard animation learning media develops animation-based micro video learning media that presents presentations with picture illustrations on a white background. The initial stages of creating whiteboard animation media are determining the material, designing slides, adding animation elements, recording sound explaining the material, and inserting recorded sound into each slide of the required material. Using whiteboard animation learning media, you can create new ideas, overcome mental obstacles, change your approach to a problem, describe a particular object, and have ideas that emerge through the student's thinking rather than taking ideas from others.